Robust Anisotropic Cellulose Hydrogels Fabricated via Strong Self-aggregation Forces for Cardiomyocytes Unidirectional Growth - Ye, Dongdong; Yang, Pengcheng; Lei, Xiaojuan; Zhang, Donghui; Li, Liangbin; Chang, Chunyu; Sun, Pingchuan; Zhang, Lina (Chemistry of materials, 2018)
The development of a facile and fast method to construct anisotropic hydrogels with the ability to induce unidirectional growth of cells remains challenging. In this work, we demonstrated anisotropic cellulose hydrogels (ACHs) that are composed of nanoscale aligned nanofibers by dissolving cotton liner pulp in alkali/urea aqueous solution. On the basis of directionally controlling the architecture of cellulose chains with a facial prestretching strategy in chemical gel state and locking the highly ordered nanostructure through the formation of close physical networks via strong self-aggregation forces among neighboring cellulose nanofibers, ACHs, combing with a long-range aligned structure, entirely differential mechanical performances along the parallel and perpendicular directions of the hydrogel orientation and optical birefringence, were constructed. The aggregation of hydrogen bonds in anisotropic and isotropic hydrogels are of significant difference, confirmed by nuclear magnetic resonance technology. Importantly, ACHs with microgroove-like structure promote the adhesion and orientation of cardiomyocytes. Our work demonstrated the bottom-up fabrication of polysaccharide-based hydrogels with anisotropic structure and properties, paving the way to potentially apply them in cardiomyocytes in vitro culture system.